2020
DOI: 10.1021/acsomega.0c03613
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal Monodisperse Microspherulite Pyrite: Novel Synthesis Process and Electrochemical Study of Its Oxidation

Abstract: A simple one-step hydrothermal method was developed to synthesize pyrite (FeS 2 ) sheet- and bulklike pyrite mineral. The Fe/S molar ratio determines the phase of FeS 2 , including pyrite and marcasite. The reaction temperature and time are key factors to regulate the structure, morphology, and size of pyrite. Scanning electron and transmission electron microscopy showed the formation of monodisperse microspherulite within 1 h reaction time, and the particles aggre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…This phenomenon was attributed to the formation of a large particulate size and agglomeration. The authors also observed through XRD analysis shown in Figure a,b that pure pyrite sheets were formed at an Fe:S ratio of 1:4, while smaller ratios of 1:1 and 1:2 gave way to marcasite formation . Similarly, Rehman et al synthesized pyrite nanoparticles through a simple hydrothermal method using ferrous sulfate and sodium thiosulfate as precursors and carrying out the reaction at 200 °C for 24 h. The results showed successful production of FeS 2 along with other phases as shown in Figure c.…”
Section: Synthesis Of Pyritementioning
confidence: 89%
See 2 more Smart Citations
“…This phenomenon was attributed to the formation of a large particulate size and agglomeration. The authors also observed through XRD analysis shown in Figure a,b that pure pyrite sheets were formed at an Fe:S ratio of 1:4, while smaller ratios of 1:1 and 1:2 gave way to marcasite formation . Similarly, Rehman et al synthesized pyrite nanoparticles through a simple hydrothermal method using ferrous sulfate and sodium thiosulfate as precursors and carrying out the reaction at 200 °C for 24 h. The results showed successful production of FeS 2 along with other phases as shown in Figure c.…”
Section: Synthesis Of Pyritementioning
confidence: 89%
“…The authors also observed through XRD analysis shown in Figure 2a,b that pure pyrite sheets were formed at an Fe:S ratio of 1:4, while smaller ratios of 1:1 and 1:2 gave way to marcasite formation. 32 Similarly, Rehman et al synthesized pyrite nanoparticles through a simple hydrothermal method using ferrous sulfate and sodium thiosulfate as precursors and carrying out the reaction at 200 °C for 24 h. The results showed successful production of FeS 2 along with other phases as shown in Figure 2c. Postsulfurization was therefore carried out for different time periods ranging from 30 min to 2 h. The study showed that postsulfurization led to an increase in the Seebeck coefficient by 2-fold along with an increase in electrical conductivity, demonstrated in Figure 2d, which was a result of an improvement in pyrite purity through phase transformations.…”
Section: ■ Synthesis Of Pyritementioning
confidence: 94%
See 1 more Smart Citation
“…The pyrite cubic lattice structure is made up of a central Fe atom that is surrounded by six S atoms in an octahedral arrangement (Figure a). In contrast, marcasite is constructed of linear chains of S 2 2– octahedra that share edges (Figure b) …”
Section: Metal Sulfides (Mss)mentioning
confidence: 99%
“…Unlike other group TMX 2 s, group‐8 TMX 2 s exhibits a different type of polymorphism as observed in Fe‐based TMX 2 s, which tend to crystallize either in the marcasite structure ( Pnnm ) or pyrite structure ( Pa 3false¯$\bar{3}$), depending on subtle variations in the chemical composition ratio, pressure, and temperature. [ 220–223 ] Despite their similar structures, the octahedra are elongated in the ab ‐plane in the former, whereas they are regular in the latter. Additionally, the pyrite lattice structure is characterized by a center‐facing TM atom, which is octahedrally coordinated by six X atoms; however, marcasite is composed of X‐atom chains that share their edges.…”
Section: Various Families Of Tmdsmentioning
confidence: 99%